Surfactin accelerates Bacillus subtilis pellicle biofilm development - Rune Overlund Stannius; Sarah Fusco; Michael S. Cowled; Ákos T. Kovács (Biofilm)
Surfactin is a biosurfactant produced by many B. subtilis strains with a wide variety of functions from lowering surface tension to allowing motility of bacterial swarms, acting as a signaling molecule, and even exhibiting antimicrobial activities. However, the impact of surfactin during biofilm formation has been debated with variable findings between studies depending on the experimental conditions.B. subtilis is known to form biofilms at the solid-air, the solid-medium, and the liquid-air interfaces, the latter of which is known as a pellicle biofilm. Pellicle formation is a complex process requiring coordinated movement to the liquid-air interface and subsequent cooperative production of biofilm matrix components to allow robust pellicle biofilm formation. This makes pellicle formation a promising model system for assaying factors in biofilm formation and regulation.Here, we assayed the influence of surfactin and additional metabolites on the timing of pellicle biofilm formation. Using time-lapse imaging, we assayed pellicle formation timing in 12 B. subtilis isolates and found that one, MB9_B4, was significantly delayed in pellicle formation by approximately 10 h. MB9_B4 was previously noted to lack robust surfactin production. Indeed, deletion of surfactin synthesis in the other isolates delayed pellicle formation. Further, pellicle delay was rescued by addition of exogeneous surfactin. Testing reporters of biofilm-related gene expression revealed that induction of pellicle formation was caused by a combination of increased gene expression of one of the biofilm components and promotion of growth.